(untitled) (REMUNOM, 2023)
Blockchain technology is an innovation that has been in development for more than a decade, but many people still do not understand its breadth of application and possibilities for various sectors. Initially used in the financial market, blockchain technology has been explored in various fields, including construction. The construction sector, traditionally slow in adopting new technologies, is beginning to recognize the potential of blockchain to manage its processes and projects more efficiently. In this article, we will discuss the potential of blockchain and smart contracts for managing construction processes and projects, as well as describe use cases and challenges to be overcome for the successful implementation of this technology in Construction 4.0.